Effects of salt stress on germination, seedling growth, osmotic adjustment, and chlorophyll fluorescence in Prosopis alba G. - Meloni, Diego Ariel (2019)
Fil: Meloni, Diego Ariel. Universidad Nacional de Santiago del Estero (Argentina)